Pengaruh Persepsi Pengusaha Kecil Dan Menengah Terhadap Penggunaan Sak Etap Di Kota Bandar Lampung (Studi Pada Sentra Kripik Segalamider Bandar Lampung) - Rosmiaty Tarmizi; Ni Luh Sartika Bugawanti (Universitas Bandar Lampung (UBL), 2013)
Accounting practices, financial accounting in particular on SMEs in Indonesia is still low and has many drawbacks. Weakness, partly due to lack of education, lack of understanding of Financial Accounting Standards (GAAP) of the owners and managers in the absence of regulations requiring the preparation of financial statements for SMEs. The main problem in this research is how the influence of perception of small and medium enterprises to the use of SAK ETAP?. The purpose of this study was to determine the effect of the perception of how small and medium enterprises to the use of SAK ETAP